A composite catalyst and its application in the synthesis of antimony-free polyester fiber

By using a composite catalyst in polyester fiber synthesis, the catalyst combines with a flame retardant cocatalyst through carboxy modified montmorillonite and loading titanium dioxide in situ by hydrothermal method, the problems of insufficient thermal stability and flame retardant performance of existing titanium catalysts in polyester fiber synthesis are solved, and the high thermal stability, crystallization and flame retardant performance of polyester fiber are improved.

CN119192550BActive Publication Date: 2025-04-29SUQIAN YIDA NEW MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411449362.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-04-29
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing titanium-based catalysts have problems such as poor hydrolysis, many side reactions, and poor thermal stability in the synthesis of polyester fibers, resulting in poor color yellowing, crystallization and high temperature resistance, and have flammable characteristics, and low limit oxygen index.

Method used

A composite catalyst is used, which is combined with a flame retardant cocatalyst through carboxy modified montmorillonite and is loaded in situ by hydrothermal method to form a catalyst with high thermal stability and flame retardant properties.

Benefits of technology

This catalyst can significantly improve the thermal stability, crystallization performance and flame retardant properties of polyester fibers, while improving the hue of polyester, shortening the polycondensation reaction time, and improving the reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088623360000091
    Figure BDA0005088623360000091
Patent Text Reader

Abstract

The invention relates to the field of polyester synthesis, and discloses a composite catalyst and application thereof in the synthesis of antimony-free polyester fiber. The invention firstly utilizes 5-carboxypentyl-triphenylphosphonium bromide to perform carboxyl modification on sodium montmorillonite, and simultaneously utilizes 1,5-naphthalenediamine, γ-ureapropyltriethoxysilane, terephthalaldehyde and DOPO as raw materials to synthesize component one, and reacts component one, 2-methylimidazole and zinc nitrate hexahydrate to prepare a flame retardant co-catalyst, and then reacts the flame retardant co-catalyst with carboxyl-modified montmorillonite to prepare functional modified montmorillonite, and finally uses the functional modified montmorillonite as a carrier and adopts a hydrothermal method to in-situ load titanium dioxide on the surface of the functional modified montmorillonite to synthesize the composite catalyst. The composite catalyst prepared by the invention shortens the polycondensation reaction time, improves the reaction efficiency, can improve the thermal stability, crystallization performance and flame retardancy of the synthesized polyester, and simultaneously improves the hue of the polyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester synthesis, and particularly relates to a composite catalyst and application thereof in the synthesis of antimony-free polyester fibers. Background Art

[0002] Polyester fiber is a synthetic fiber obtained by spinning polyester formed by the condensation of organic dibasic acids and diols. Due to its excellent modulus, strength, elasticity, shape retention and heat resistance, it has become one of the most widely used and most consumed chemical fiber varieties, accounting for more than 50% of the total textile fiber, and is commonly used in home furnishings, clothing, industrial textiles and other fields.

[0003] The synthesis process of polyester fiber includes esterification and polycondensation stages, in which catalysts play a vital role. At present, the most widely used ones are antimony, germanium and titanium catalysts. Antimony catalysts have high catalytic activity, few side reactions and low prices. They have basically achieved large-scale industrialization in the field of polyester. However, antimony compounds are prone to produce "gray fog" when used as catalysts. They coexist with arsenic in nature and are toxic substances. They do not conform to the green and healthy environmental protection concept. The polyester products prepared by germanium catalysts have better hue, but the scarcity of germanium resources in nature leads to high prices. It is difficult to control the catalytic activity during the reaction process, resulting in no industrial application. They are mainly used in the film-forming process. Titanium catalysts are abundant in nature, non-toxic and harmless, and have high catalytic activity, so they have received widespread attention as a replacement for other catalysts.

[0004] The titanium-based catalysts used in the prior art have the problems of being easily hydrolyzed, inducing many side reactions, and having poor thermal stability, resulting in the synthetic polyester fiber products being yellow in color, having poor crystallization properties and high temperature resistance, which to a certain extent limits their application in actual production. In addition, conventional polyester fibers are flammable, have a low limiting oxygen index, and are very prone to dripping during combustion, which can easily cause secondary combustion, limiting their further application in actual production. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a composite catalyst and its application in the synthesis of antimony-free polyester fiber. The prepared composite catalyst shortens the condensation reaction time, improves the reaction efficiency, can improve the thermal stability, crystallization performance, and flame retardant properties of the synthetic polyester, and at the same time improves the hue of the polyester.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A composite catalyst, wherein the composite catalyst is prepared by grafting a flame retardant co-catalyst onto carboxyl-modified montmorillonite and then in-situ loading titanium dioxide by a hydrothermal method; wherein the flame retardant co-catalyst is prepared by synthesizing component one by using 1,5-naphthalenediamine, γ-ureapropyltriethoxysilane, terephthalaldehyde and DOPO as raw materials, and then reacting component one, 2-methylimidazole and zinc nitrate hexahydrate;

[0008] The preparation method comprises the following steps:

[0009] A. Sodium montmorillonite is ultrasonically dispersed in deionized water, 5-carboxypentyl-triphenylphosphonium bromide is added and ultrasonically dispersed uniformly, and the mixture is stirred at 75-85° C. for 3-5 hours. After the reaction is completed, the mixture is filtered, washed, and dried to prepare carboxyl-modified montmorillonite;

[0010] B. 1,5-naphthalenediamine and γ-ureapropyltriethoxysilane are placed in a reactor, and ethanol solvent is added for ultrasonic dispersion. Terpene dialdehyde is dissolved in ethanol and added to the reactor, and refluxed at 55-70°C for 3-5h. DOPO is dissolved in ethanol and added to the reactor, and the temperature is raised to 75-85°C for continuous reaction for 4-6h to obtain component 1. 2-methylimidazole is dissolved in methanol and added to component 1, and stirred at 45-55°C for 1-2h. Zinc nitrate hexahydrate is dissolved in methanol and added to the reactor, and reacted at 35-40°C for 1-2h. After the reaction is completed, the flame retardant catalyst is prepared by centrifugation, washing and drying.

[0011] C. Ultrasonic dispersion of carboxyl modified montmorillonite in deionized water to obtain a dispersion, deionized water, EDC and NHS are mixed evenly to obtain a mixed solution, the mixed solution is added to the dispersion, and then a flame retardant promoter is added, and the mixture is stirred at 35 to 55° C. for 4 to 6 hours. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain a functional modified montmorillonite;

[0012] D. Take the functional modified montmorillonite and ultrasonically disperse it in deionized water to obtain a dispersion. Take a sodium hydroxide solution in a reactor, control the water bath temperature to 50-65°C, slowly drop the titanium tetrachloride solution, and then add the obtained dispersion into the reactor. Heat it to 80-90°C and continue stirring to react for 1-3 hours. After the reaction is completed, adjust the pH value of the system to 5-6, filter, wash and dry to prepare a composite catalyst.

[0013] Preferably, in step A, the mass ratio of sodium montmorillonite to 5-carboxypentyl-triphenylphosphonium bromide is 1:0.1-1.

[0014] Preferably, in step B, the molar ratio of 1,5-naphthalenediamine, γ-ureapropyltriethoxysilane, terephthalaldehyde, DOPO, 2-methylimidazole and zinc nitrate hexahydrate is 1:1-2:1-3:2-4:2-2.4:0.35-0.4.

[0015] Preferably, in step C, the mass ratio of the carboxyl-modified montmorillonite to the flame retardant promoter is 1:0.05-0.5.

[0016] Preferably, the molar ratio of EDC to NHS in step C is 4-6:1.

[0017] Preferably, the concentration of the sodium hydroxide solution in step D is 2-5 mol / L.

[0018] Preferably, the concentration of the titanium tetrachloride solution in step D is 2-4 mol / L, and the dropping speed of the titanium tetrachloride solution is 3-5 mL / min.

[0019] Preferably, the addition ratio of the functional modified montmorillonite and deionized water contained in the dispersion in step D is 5-10 g: 60-100 mL, and the volume ratio of the dispersion, sodium hydroxide solution and titanium tetrachloride solution is 2-3: 2-2.5: 1-2.

[0020] The application of the composite catalyst as described above in the synthesis of antimony-free polyester fiber.

[0021] Preferably, the polyester fiber is one of PET fiber, PTT fiber and PBT fiber.

[0022] Beneficial effects of the present invention:

[0023] The invention firstly utilizes 5-carboxypentyl-triphenylphosphonium bromide with good heat resistance to perform carboxyl modification on sodium montmorillonite. Meanwhile, the invention utilizes 1,5-naphthalenediamine, γ-ureapropyltriethoxysilane, terephthalaldehyde and DOPO as raw materials to synthesize component one, reacts the aldehyde group at one end of terephthalaldehyde with the amino group in the structure of γ-ureapropyltriethoxysilane to generate an N=HC bond, reacts the aldehyde group at the other end of terephthalaldehyde with the amino group at one end of the structure of 1,5-naphthalenediamine to generate an N=HC bond, and then utilizes the PH bond in the DOPO structure and the N=HC bond to generate an addition reaction to prepare component one with flame retardant effect, wherein 1,5-naphthalenediamine has high thermal stability and can release smoke and flame retardant gas that inhibits combustion at high temperature. DOPO is one of the organic phosphorus flame retardants, and DOPO and 1,5-naphthalenediamine have a synergistic flame retardant effect. In addition, the invention utilizes 2-methylimidazole and zinc nitrate hexahydrate to coordinate to form a highly regular The mesoporous structure ZIF-8 is prepared, and then the silicon hydroxyl group in the structure of component one is grafted with the metal organic material ZIF-8, wherein ZIF-8 contains metal ions and a high content of nitrogen, and can be used as a nitrogen-containing flame retardant and has a catalytic effect, to prepare a flame retardant co-catalyst, and then the amino group in the flame retardant co-catalyst structure is subjected to an amidation reaction with the carboxyl-modified montmorillonite, thereby introducing the flame retardant co-catalyst into the montmorillonite layered structure, increasing the montmorillonite layer spacing, which is beneficial to the dispersion of the montmorillonite, and adding the functional modified montmorillonite to the matrix material can improve the thermal properties and crystallization properties of the material, and finally, the functional modified montmorillonite is used as a carrier, and the composite catalyst is synthesized by in-situ loading titanium dioxide on the surface of the functional modified montmorillonite by a hydrothermal method, which solves the problems of uneven dispersion and easy agglomeration of titanium dioxide, and at the same time greatly improves the catalytic efficiency, avoids the problem of easy yellowing of polyester fiber products, and in addition, the thermal stability, crystallization properties and flame retardancy of the synthesized polyester are improved. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1 A method for preparing a composite catalyst comprises the following steps:

[0026] A. Take 10g of sodium montmorillonite and ultrasonically disperse it in 200mL of deionized water, add 4.8g of 5-carboxypentyl-triphenylphosphonium bromide and ultrasonically disperse it evenly, place it at 80°C and stir to react for 4h. After the reaction is completed, filter, wash and dry it to prepare carboxyl-modified montmorillonite;

[0027] B. Take 3.95g 1,5-naphthalenediamine and 13.21g γ-ureapropyltriethoxysilane in a reactor, add 50mL ethanol solvent and ultrasonically disperse them evenly, take 10.06g terephthalaldehyde and dissolve it in 100mL ethanol and add it to the reactor, place it at 65°C for reflux reaction for 4h, then take 21.62g DOPO and dissolve it in 100mL ethanol and add it to the reactor, heat it to 80°C and continue to react for 5h to obtain component one, take 4.76g 2-methylimidazole and dissolve it in 100mL methanol and add it to component one, place it at 55°C and stir for 2h, then take 2.97g zinc nitrate hexahydrate and dissolve it in 30mL methanol and continue to add it to the reactor, place it at 40°C for reaction for 2h, and after the reaction is completed, centrifuge, wash and dry to prepare a flame retardant catalyst;

[0028] C. Take 10g of carboxyl-modified montmorillonite and ultrasonically disperse it in 200mL of deionized water to obtain a dispersion, take 30mL of deionized water to prepare a mixed solution according to the molar ratio of EDC and NHS of 5:1, add the mixed solution to the dispersion, then add 0.5g of flame retardant promoter, place it at 40°C and stir for 5h, after the reaction is completed, centrifuge, wash and dry to prepare functional modified montmorillonite;

[0029] D. Take 10g of functional modified montmorillonite and ultrasonically disperse it in 100mL of deionized water to obtain a dispersion. Take 100mL of 2.5mol / L sodium hydroxide solution in a reactor, control the water bath temperature to 50°C, slowly add 50mL of 2.5mol / L titanium tetrachloride solution at a dropping rate of 4mL / min, and then add the obtained dispersion to the reactor. Heat it to 85°C and continue stirring to react for 3h. After the reaction is completed, adjust the pH value of the system to 5, filter, wash and dry to prepare a composite catalyst.

[0030] Embodiment 2 A method for preparing a composite catalyst comprises the following steps:

[0031] A. Take 10g of sodium montmorillonite and ultrasonically disperse it in 200mL of deionized water, add 4.8g of 5-carboxypentyl-triphenylphosphonium bromide and ultrasonically disperse it evenly, place it at 80°C and stir to react for 4h. After the reaction is completed, filter, wash and dry it to prepare carboxyl-modified montmorillonite;

[0032] B. Take 3.95g 1,5-naphthalenediamine and 13.21g γ-ureapropyltriethoxysilane in a reactor, add 50mL ethanol solvent and ultrasonically disperse them evenly, take 10.06g terephthalaldehyde and dissolve it in 100mL ethanol and add it to the reactor, place it at 65°C for reflux reaction for 4h, then take 21.62g DOPO and dissolve it in 100mL ethanol and add it to the reactor, heat it to 80°C and continue to react for 5h to obtain component one, take 4.76g 2-methylimidazole and dissolve it in 100mL methanol and add it to component one, place it at 55°C and stir for 2h, then take 2.97g zinc nitrate hexahydrate and dissolve it in 30mL methanol and continue to add it to the reactor, place it at 40°C for reaction for 2h, and after the reaction is completed, centrifuge, wash and dry to prepare a flame retardant catalyst;

[0033] C. Take 10g of carboxyl-modified montmorillonite and ultrasonically disperse it in 200mL of deionized water to obtain a dispersion, take 30mL of deionized water to prepare a mixed solution according to the molar ratio of EDC and NHS of 5:1, add the mixed solution to the dispersion, then add 5g of flame retardant promoter, place it at 40°C and stir for 5h, after the reaction is completed, centrifuge, wash and dry to prepare functional modified montmorillonite;

[0034] D. Take 10g of functional modified montmorillonite and ultrasonically disperse it in 100mL of deionized water to obtain a dispersion. Take 100mL of 2.5mol / L sodium hydroxide solution in a reactor, control the water bath temperature to 50°C, slowly add 50mL of 2.5mol / L titanium tetrachloride solution at a dropping rate of 4mL / min, and then add the obtained dispersion to the reactor. Heat it to 85°C and continue stirring to react for 3h. After the reaction is completed, adjust the pH value of the system to 5, filter, wash and dry to prepare a composite catalyst.

[0035] Embodiment 3 A method for preparing a composite catalyst comprises the following steps:

[0036] A. Take 10g of sodium montmorillonite and ultrasonically disperse it in 200mL of deionized water, add 4.8g of 5-carboxypentyl-triphenylphosphonium bromide and ultrasonically disperse it evenly, place it at 80°C and stir to react for 4h. After the reaction is completed, filter, wash and dry it to prepare carboxyl-modified montmorillonite;

[0037] B. Take 3.95g 1,5-naphthalenediamine and 13.21g γ-ureapropyltriethoxysilane in a reactor, add 50mL ethanol solvent and ultrasonically disperse them evenly, take 10.06g terephthalaldehyde and dissolve it in 100mL ethanol and add it to the reactor, place it at 65°C for reflux reaction for 4h, then take 21.62g DOPO and dissolve it in 100mL ethanol and add it to the reactor, heat it to 80°C and continue to react for 5h to obtain component one, take 4.76g 2-methylimidazole and dissolve it in 100mL methanol and add it to component one, place it at 55°C and stir for 2h, then take 2.97g zinc nitrate hexahydrate and dissolve it in 30mL methanol and continue to add it to the reactor, place it at 40°C for reaction for 2h, and after the reaction is completed, centrifuge, wash and dry to prepare a flame retardant catalyst;

[0038] C. Take 10g of carboxyl-modified montmorillonite and ultrasonically disperse it in 200mL of deionized water to obtain a dispersion, take 30mL of deionized water to prepare a mixed solution according to the molar ratio of EDC and NHS of 5:1, add the mixed solution to the dispersion, then add 0.5g of flame retardant promoter, place it at 40°C and stir for 5h, after the reaction is completed, centrifuge, wash and dry to prepare functional modified montmorillonite;

[0039] D. Take 5g of functional modified montmorillonite and ultrasonically disperse it in 60mL of deionized water to obtain a dispersion. Take 75mL of 2.5mol / L sodium hydroxide solution in a reactor, control the water bath temperature to 50°C, slowly add 45mL of 2.5mol / L titanium tetrachloride solution at a dropping rate of 4mL / min, and then add the obtained dispersion to the reactor. Heat to 85°C and continue stirring to react for 3h. After the reaction is completed, adjust the pH value of the system to 5, filter, wash and dry to prepare a composite catalyst.

[0040] Comparative Example 1 A method for preparing a composite catalyst comprises the following steps:

[0041] 10 g of montmorillonite was ultrasonically dispersed in 100 mL of deionized water to obtain a dispersion, 100 mL of 2.5 mol / L sodium hydroxide solution was placed in a reactor, the water bath temperature was controlled at 50° C., 50 mL of 2.5 mol / L titanium tetrachloride solution was slowly added dropwise at a rate of 4 mL / min, and the obtained dispersion was added to the reactor. The temperature was raised to 85° C. and the reaction was continued under stirring for 3 h. After the reaction was completed, the pH value of the system was adjusted to 5, and the composite catalyst was prepared by suction filtration, washing, and drying.

[0042] Comparative Example 2 A method for preparing a composite catalyst comprises the following steps:

[0043] A. Take 10g of sodium montmorillonite and ultrasonically disperse it in 200mL of deionized water, add 4.8g of 5-carboxypentyl-triphenylphosphonium bromide and ultrasonically disperse it evenly, place it at 80°C and stir to react for 4h. After the reaction is completed, filter, wash and dry it to prepare carboxyl-modified montmorillonite;

[0044] B. 3.95 g of 1,5-naphthalenediamine and 13.21 g of γ-ureapropyltriethoxysilane were placed in a reactor, 50 mL of ethanol solvent was added for ultrasonic dispersion, 10.06 g of terephthalaldehyde was dissolved in 100 mL of ethanol and added to the reactor, and refluxed at 65° C. for 4 h, and then 21.62 g of DOPO was dissolved in 100 mL of ethanol and added to the reactor, and the temperature was raised to 80° C. and the reaction was continued for 5 h to obtain component 1;

[0045] C. Take 10g of carboxyl-modified montmorillonite and ultrasonically disperse it in 200mL of deionized water to obtain a dispersion. Take 30mL of deionized water to prepare a mixed solution according to the molar ratio of EDC and NHS of 5:1. Add the mixed solution to the dispersion, then add 0.5g of component 1, stir and react at 40°C for 5h. After the reaction is completed, centrifuge, wash and dry to prepare functional modified montmorillonite.

[0046] D. Take 10g of functional modified montmorillonite and ultrasonically disperse it in 100mL of deionized water to obtain a dispersion. Take 100mL of 2.5mol / L sodium hydroxide solution in a reactor, control the water bath temperature to 50°C, slowly add 50mL of 2.5mol / L titanium tetrachloride solution at a dropping rate of 4mL / min, and then add the obtained dispersion to the reactor. Heat it to 85°C and continue stirring to react for 3h. After the reaction is completed, adjust the pH value of the system to 5, filter, wash and dry to prepare a composite catalyst.

[0047] Comparative Example 3 uses the traditional titanium-based catalyst antimony trioxide as the composite catalyst.

[0048] Performance Testing

[0049] (a) Synthesis of PET: 350 g of terephthalic acid and 170 g of ethylene glycol were weighed, and 2.6 g of the composite catalyst prepared in Examples 1-3 and Comparative Examples 1-3 were weighed respectively and added to the ethylene glycol, and ultrasonic dispersion was performed for 30 min. Then the above raw materials were added to a polyester reactor, and the air in the reactor was replaced with nitrogen twice. Then the temperature was raised to 260° C. for esterification reaction. When the tower top temperature reached 120° C., esterification water began to be discharged, and water was collected with a measuring cylinder. When the theoretical water output was reached, preparation for polycondensation reaction was started. The initial stage was the pre-polycondensation stage. The jacket temperature of the reactor was raised to 270° C., and vacuum was evacuated by a vacuum pump. The reactor was slowly evacuated to -100 Pa through the fine adjustment valve of the reactor to reach the high vacuum stage. Then the jacket temperature was set to 280° C., and the polycondensation reaction was carried out when the vacuum degree in the reactor was lower than 50 Pa. When the viscosity reached the required value, the material was discharged. The polymer PET after the reaction was cooled with cold water, and then cut into polyester chips by a pelletizer.

[0050] (b) Performance testing: The chromaticity values ​​(L, a, b) of PET were measured using a fully automatic colorimeter; the outflow time of the PET solution was determined using an Ubbelohde viscometer to calculate the intrinsic viscosity; the thermal stability of PET was tested using a thermogravimetric analyzer; the crystallization properties of polyester PET were tested using a differential scanning calorimeter; the flame retardant properties of PET were evaluated using the limiting oxygen index and vertical combustion tests, and the data results are shown in Table 1.

[0051] Table 1 Test results of sample performance

[0052]

[0053] It can be seen from the data results in Table 1 that the composite catalysts prepared in Examples 1-3 of the present invention shorten the polycondensation reaction time, improve the reaction efficiency, increase the chromaticity L value of the synthesized PET, improve the hue, and have a high initial decomposition temperature, good heat resistance, a low cold crystallization temperature, a faster crystallization rate and good crystallization ability. In addition, the limiting oxygen index reaches more than 30%, the vertical combustion level reaches V-0, and has excellent flame retardant properties. Among them, non-functional modified montmorillonite is added to the composite catalyst prepared in Comparative Example 1, and antimony trioxide catalyst is added in Comparative Example 2. It is measured that the thermal stability and crystallization performance of the synthetic PET in Comparative Example 1-2 are worse than those in Example 1-3, and the hue and flame retardancy of PET are lower than those in Example 1-3, indicating that the composite catalyst prepared in Example 1-3 can improve the thermal stability, crystallization performance, and flame retardancy of the synthetic PET, shorten the polycondensation time, improve the reaction efficiency, and improve the hue of PET. In Comparative Example 2, 2-methylimidazole and zinc nitrate hexahydrate are not added, and the initial decomposition temperature and limiting oxygen index are lower than those in Example 1-3, and the polycondensation time is longer than that in Example 1-3, indicating that the metal organic material ZIF-8 can be used as a nitrogen-containing flame retardant and has a catalytic effect.

[0054] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0055] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A composite catalyst, characterized in that: The composite catalyst is prepared by grafting a flame retardant co-catalyst onto carboxyl-modified montmorillonite, and then in-situ loading titanium dioxide by a hydrothermal method; wherein the flame retardant co-catalyst is prepared by synthesizing component one by using 1,5-naphthalenediamine, γ-ureapropyltriethoxysilane, terephthalaldehyde and DOPO as raw materials, and then reacting component one, 2-methylimidazole and zinc nitrate hexahydrate; The preparation method comprises the following steps: A. Sodium montmorillonite is ultrasonically dispersed in deionized water, 5-carboxypentyl-triphenylphosphonium bromide is added and ultrasonically dispersed uniformly, and the mixture is stirred at 75-85° C. for 3-5 hours. After the reaction is completed, the mixture is filtered, washed, and dried to prepare carboxyl-modified montmorillonite; B. 1,5-naphthalenediamine and γ-ureapropyltriethoxysilane are placed in a reactor, and ethanol solvent is added for ultrasonic dispersion. Terpene dialdehyde is dissolved in ethanol and added to the reactor, and refluxed at 55-70°C for 3-5h. DOPO is dissolved in ethanol and added to the reactor, and the temperature is raised to 75-85°C for continuous reaction for 4-6h to obtain component 1. 2-methylimidazole is dissolved in methanol and added to component 1, and stirred at 45-55°C for 1-2h. Zinc nitrate hexahydrate is dissolved in methanol and added to the reactor, and reacted at 35-40°C for 1-2h. After the reaction is completed, the flame retardant catalyst is prepared by centrifugation, washing and drying. C. Ultrasonic dispersion of carboxyl modified montmorillonite in deionized water to obtain a dispersion, deionized water, EDC and NHS are mixed evenly to obtain a mixed solution, the mixed solution is added to the dispersion, and then a flame retardant promoter is added, and the mixture is stirred at 35 to 55° C. for 4 to 6 hours. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain a functional modified montmorillonite; D. Take the functional modified montmorillonite and ultrasonically disperse it in deionized water to obtain a dispersion. Take a sodium hydroxide solution in a reactor, control the water bath temperature to 50-65°C, slowly drop the titanium tetrachloride solution, and then add the obtained dispersion into the reactor. Heat it to 80-90°C and continue stirring to react for 1-3 hours. After the reaction is completed, adjust the pH value of the system to 5-6, filter, wash and dry to prepare a composite catalyst.

2. The composite catalyst according to claim 1, characterized in that In the step A, the mass ratio of sodium montmorillonite to 5-carboxypentyl-triphenylphosphonium bromide is 1:0.1-1.

3. The composite catalyst according to claim 1, characterized in that In the step B, the molar ratio of 1,5-naphthalenediamine, γ-ureapropyltriethoxysilane, terephthalaldehyde, DOPO, 2-methylimidazole and zinc nitrate hexahydrate is 1:1-2:1-3:2-4:2-2.4:0.35-0.

4.

4. The composite catalyst according to claim 1, characterized in that In the step C, the mass ratio of the carboxyl-modified montmorillonite to the flame retardant promoter is 1:0.05-0.

5.

5. The composite catalyst according to claim 1, characterized in that The molar ratio of EDC to NHS in step C is 4-6:

1.

6. The composite catalyst according to claim 1, characterized in that The concentration of the sodium hydroxide solution in step D is 2-5 mol / L.

7. The composite catalyst according to claim 1, characterized in that The concentration of the titanium tetrachloride solution in step D is 2-4 mol / L, and the dropping speed of the titanium tetrachloride solution is 3-5 mL / min.

8. The composite catalyst according to claim 1, characterized in that In the step D, the addition ratio of the functional modified montmorillonite and deionized water contained in the dispersion is 5-10 g: 60-100 mL, and the volume ratio of the dispersion, the sodium hydroxide solution and the titanium tetrachloride solution is 2-3: 2-2.5: 1-2.

9. Use of the composite catalyst according to any one of claims 1 to 8 in the synthesis of antimony-free polyester fiber.

10. The use according to claim 9, characterized in that: The polyester fiber is one of PET fiber, PTT fiber and PBT fiber.

Citation Information

Patent Citations

  • Method for preparing flame-retardant and anti-dripping polyester fiber

    CN101851811A

  • Preparation method of fast crystallization type polyester

    CN114874424A